Mediating role of self-regulated learning strategies on peer learning, online learning satisfaction and academic achievement among students of a private university in Malaysia - Lim, Chee Leong (2020)
Challenges students face in the online component of blended learning, especially in the areas related to self-regulation challenges have deferred them in achieving their learning goals. Besides, improper utilization of online peer learning strategy has also been identified as an inherent problem related to self-regulation challenges in the blended learning environment. Therefore this study adopted Zimmerman’s perspective of SRL which draws from social cognitive theory and Bandura's self-efficacy theory to determine the influence of Self-Regulated Learning (SRL) strategies and peer learning on students’ learning satisfaction and academic achievement. This study adopted a correlational research design to investigate the possibility of relationships between these variables in this case study. In this case study, the sample was selected based on proportional stratified sampling method in a Malaysian private university. Of the 409 respondents, only 347 were valid for data analysis, forming a usable case of 84.84%. Structural Equation Model (SEM) analysis was used to examine the relationship between the constructs in the hypothesised model. The results unveiled that students’ abilities to self-regulate their learning and to learn effectively with peer accounted for 41% of the variation in learning satisfaction. From the direct effect of the SEM analysis, peer learning was found to have significantly influenced students’ SRL strategy, while the use of SRL strategy was found to have a positive and statistically significant effect on their learning satisfaction. Moreover, the findings from the Bootstrapping test concurred that SRL fully mediated the relationship between peer learning and learning satisfaction. Besides, the results attained also produced a model that predicted 25.1% of the variation in the students’ academic achievement. These results explained that peer learning contributed significantly to their academic achievement in blended learning courses. However, there was no significant relationship between peer learning and learning satisfaction. For the moderation test, the Multi-Group Analysis showed that academic discipline has a significant moderating effect on the relationship between peer learning and academic achievement, particularly in the discipline related the science courses. However, the gender difference was not evident in blended learning courses. This study uncovers and contributes to the existing body of knowledge for blended learning in several ways. In terms of theoretical contribution, this study contributes to the literature on both peer learning and learning satisfaction, by introducing SRL as the mediating variable that interacts with peer learning to influence students’ satisfaction. It proposes an integrated, coherent and actionable framework covering a variety of constructs, including SRL strategy, peer learning, learning satisfaction and academic achievement in the context of blended learning. In addition, it also provides insights for universities as to where future efforts need to be directed, especially in the areas related to the improvement of the facilities and infrastructure for blended learning implementation. It also discusses the practical implications as well as suggests several instructional approaches designed to facilitate the development of students’ SRL strategy and peer learning through the use of educational technologies.